Pengaruh Restrukturisasi Organisasi, Social Media Marketing Dan Work Engagement Terhadap Kinerja Pegawai Lembaga Sertifikasi Internasional Jakarta - Sudarwanto, Sudarwanto; Hermawan, Eric (Jurnal Ilmu Administrasi Publik, 2024)
The independent variable of organizational restructuring that has been adjusted by managers can streamline costs, increase productivity and income, improve employee welfare, increase shareholder wealth, increase efficiency and ultimately improve employee performance. Thus we use organizational restructuring variables to examine employee performance at the Jakarta International Certification Institute. The second independent variable is Social Media Marketing which is used because social media is a form of marketing that is used to create awareness, recognition, memory and even action towards a brand, product, business, individual or group either directly or indirectly by using tools from the web. such as blogging, microblogging, and social networking. After that, it is complemented by Work engagement reflecting intensive involvement in work, employees who own it, have more attention to the company, think about important details, are immersed in their work, feel the experience of being immersed in work so that they forget about time and reduce all kinds of distractions at work. These three independent variables are tried to determine their effect either partially or simultaneously. Working with SPSS to determine simple regression equations and multiple linear regression equations after the data used was tested with validity, reliability, normality, multicollinearity and heteroscedasticity tests. The sample in this study was 100 people from 132 population by taking the sample determination error according to the Slovin formula of e = 0.005. The results of the study found that the influence of organizational restructuring, social media marketing and work engagement, both partial and simultaneous, was significant and positive.